An Unusual Etiology of Cerebellar Ataxia. (9th March 2020) - Kaiser, Ryan Sohail; Khemka, Arpita; Roy, Oishik; Das, Subhash; Datta, Kalpana
Cerebellar ataxia, which is the lack of coordination, has a number of causes none of which are as uncommon or unheard of as Scrub typhus. Scrub typhus very rarely presents itself with CNS manifestations. Here, we present the case of a 7-year-old girl from the Hooghly district in West Bengal, who presented to us with the history of fever, cerebellar signs, and sudden onset of visual loss. She was ultimately diagnosed with scrub typhus cerebellitis.